Endoplasmic Reticulum–Mitochondrial Ca2+ Fluxes Underlying Cancer Cell Survival - Ivanova, Hristina; Kerkhofs, Martijn; La Rovere, Rita M.; Bultynck, Geert (Frontiers in Oncology, 2017)
Calcium ions (Ca2+) are crucial, ubiquitous, intracellular second messengers required for functional mitochondrial metabolism during uncontrolled proliferation of cancer cells. The mitochondria and the endoplasmic reticulum (ER) are connected via “mitochondria-associated ER membranes” (MAMs) where ER-mitochondria Ca2+ transfer occurs, impacting the mitochondrial biology related to several aspects of cellular survival, autophagy, metabolism, cell death sensitivity and metastasis, all cancer hallmarks. Cancer cells appear addicted to these constitutive ER-mitochondrial Ca2+ fluxes for their survival since they drive the TCA cycle and the production of mitochondrial substrates needed for nucleoside synthesis and proper cell cycle progression. In addition to this, the mitochondrial Ca2+ uniporter (MCU) and mitochondrial Ca2+ have been linked to hypoxia-inducible factor 1α (HIF1α signaling, enabling metastasis and invasion processes, but they can also contribute to cellular senescence induced by oncogenes and replication. Finally, proper ER-mitochondrial Ca2+ transfer seems to be a key event in the cell death response of cancer cells exposed to chemotherapeutics. In this review, we discuss the emerging role of ER-mitochondrial Ca2+ fluxes underlying these cancer-related features.